Ethiopia Rising : Aspiring to Become a Carbon Neutral Middle Income Manufacturing Hub by 2025 - Kim, Jim Yong (2016)
Remarks delivered by Jim Yong Kim, President of the World Bank Group, discuss Ethiopia’s commitment to climate action, the role of industrialization in delivering development, and bringing these together for low-carbon, equitable growth. He speaks about the government’s promotion of low-carbon growth, poverty reduction, and climate resilience to tackle the impact of climate changes. He talks about the crucial component of Ethiopia’s drive for growth and transformation will be the development of a vibrant manufacturing and industrial base, which creates jobs for growing urban areas. The World Bank Group is working with the government to ensure that new industrial parks make use of recycled water and renewable resources, develop green areas, and reflect upgraded environmental standards and inspection systems.